The Importance of Autonomous, Self-Regulated Learning in Primary Initial Teacher Training - Oates, Sue (Frontiers in Education, 2019)
This article grew from the author’s doctoral study into the development of self-regulated learning (SRL) at the end of the primary school. A brief outline of SRL is included to provide the context for this article. The focus of learning in schools is seen as shifting from a knowledge-based focus to a skills-based curriculum as the role of the teacher adapts to the changing nature of education. Work on collaborative enquiry learning and the inclusion of pupil voice are also factors in this paradigm shift in teaching. Much of the previous research in the area of self-regulation has focused on older learners. However, interest in developing SRL throughout the primary years of schooling is growing. Initially the study focused on considering the curriculum as the driver of the development of self-regulated learning. However, when analysing the pupil and teacher questionnaire results from a variety of schools it became apparent that the teacher-pupil relationship was central to the initiation and support of autonomous learning irrespective of the curricula background of the school. The teacher’s role is viewed as paramount in the development of self-regulated learning. This article moves to focus on the preparation teachers receive in their training to support them through facilitating students to become self-regulated, autonomous learners. Teacher training is seen as requiring the incorporation of self-regulation, autonomy and the notion of lifelong learning at the heart of the courses offered to student teachers. Student teachers should be viewed as learning about self-regulation as lifelong learners themselves and teacher training practices need to change to reflect a more active and collaborative pedagogy. There is discussion of the more constructivist approaches teacher trainers can utilise to engage their students, which includes instructing their teaching students in ways, which reflect the strategies required for the students to employ with their classes.